Narrowing mortality gap between men and women over two decades: a registry-based study in Ontario, Canada. Issue 11 (14th November 2016) - Rosella, Laura C; Calzavara, Andrew; Frank, John W; Fitzpatrick, Tiffany; Donnelly, Peter D; Henry, David
Abstract : Background: Historically, women have lower all-cause mortality than men. It is less understood that sex differences have been converging, particularly among certain subgroups and causes. This has implications for public health and health system planning. Our objective was to analyse contemporary sex differences over a 20-year period. Methods: We analysed data from a population-based death registry, the Ontario Registrar's General Death file, which includes all deaths recorded in Canada's most populous province, from 1992 to 2012 (N=1 710 080 deaths). We calculated absolute and relative mortality sex differences for all-cause and cause-specific mortality, age-adjusted and age-specific, including the following causes: circulatory, cancers, respiratory and injuries. We used negative-binomial regression of mortality on socioeconomic status with direct age adjustment for the overall population. Results: In the 20-year period, age-adjusted mortality dropped 39.2% and 29.8%, respectively, among men and women. The age-adjusted male-to-female mortality ratio dropped 41.4%, falling from 1.47 to 1.28. From 2000 onwards, all-cause mortality rates of high-income men were lower than those seen among low-income women. Relative mortality declines were greater among men than women for cancer, respiratory and injury-related deaths. The absolute decline in circulatory deaths was greater among men, although relative deciles were similar to women. The largest absolute mortality gains were seen among men over the age of 85 years. Conclusions: The large decline in mortality sex ratios in a Canadian province with universal healthcare over two decades signals an important population shift. These narrowing trends varied according to cause of death and age. In addition, persistent social inequalities in mortality exist and differentially affect men and women. The observed change in sex ratios has implications for healthcare and social systems.